The geology of the Dwars river fragment and the ore-minerals of the magnetite-deposit of Kennedy's vale 361 kt. Eastern Transvaal - Van Rensburg, Willem Cornelius (University of Pretoria, 2024)
Dissertation (MSc (Geology))--University of Pretoria, 1962.